2014
DOI: 10.3923/ijb.2015.21.26
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Potential of Terminalia chebula by Hydrogen Peroxide Induced Oxidative Stress in THP-1 Cell Line

Abstract: A B S T R A C T Diseases caused due to 'oxidative stress' initiated by Reactive Oxygen Species (ROS) is growing at an alarming rate. Several medicinal herbs explored till date were reported to possess numerous pharmacological properties used for combating different diseases. The present study was undertaken to investigate the inhibitory potential of Terminalia chebula by H 2 O 2 induced oxidative stress in THP-1 cell line and also the presence of the marker compounds in T. chebula was confirmed by High Perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…71 Our study found that T chebula extract suppressed ROS production in H 2 O 2 -induced human monocytic U-937 cells. This is consistent with previous findings that T chebula extract, a source of polyphenols, tannins, and triterpenes, showed a marked decrease in intracellular ROS production in H 2 O 2 -induced human leukemia monocytic THP-1 cells 72 and in H 2 O 2 -induced rat pheochromocytoma PC12 cells. 73 It is noteworthy that the antioxidant effects of T chebula extract are mediated by its polyphenol compounds and flavonoids, 32 such as 2,4-chebulyl- β-D-glucopyranose, 1,6-di- O -galloyl-β-D-glucose, 74 quercetin, 75 gallic acid, 17 ellagic acid, 18 chebulinic acid, casuarinin, and chelanin.…”
Section: Discussionsupporting
confidence: 93%
“…71 Our study found that T chebula extract suppressed ROS production in H 2 O 2 -induced human monocytic U-937 cells. This is consistent with previous findings that T chebula extract, a source of polyphenols, tannins, and triterpenes, showed a marked decrease in intracellular ROS production in H 2 O 2 -induced human leukemia monocytic THP-1 cells 72 and in H 2 O 2 -induced rat pheochromocytoma PC12 cells. 73 It is noteworthy that the antioxidant effects of T chebula extract are mediated by its polyphenol compounds and flavonoids, 32 such as 2,4-chebulyl- β-D-glucopyranose, 1,6-di- O -galloyl-β-D-glucose, 74 quercetin, 75 gallic acid, 17 ellagic acid, 18 chebulinic acid, casuarinin, and chelanin.…”
Section: Discussionsupporting
confidence: 93%
“…Herbal drugs are difficult to standardize than the modern drugs mainly as they are usually obtainable as a mixture of several chemical constituents present in each extract (Antignac et al, 2011). Our previous studies demonstrated Gas Chromatography–Mass Spectrometry (GC–MS) based profiling of M. oleifera stem bark revealing presence of phytoconstituents like octadecenoic acid, esters (ethyl and methyl), dodecane, eicosane 2, isopropyl myristate, hexadecanoic acid, azulene, quinoline, n‐hexadecanoic acid, benzoic acid, stigmasterol, lupeol, β‐sitosterol (Minakshi et al, 2015). Most of these compounds like azulene, quinoline, phytosterols (β‐sitosterol, stigmasterol), and lupeol are known for their anti‐inflammatory, anti‐obesity, and lipid‐lowering properties.…”
Section: Resultsmentioning
confidence: 99%
“…With this major health issue on the forefront, scientific research has focused on the discovery of naturally derived compounds that would reverse the present scenario. The WHO recommends the necessity for safe, effective, and quality herbal formulations based on guidelines especially when there is a lack of safety of modern drugs (Minakshi et al, 2015). Therefore, the urge to search for therapies that are safe and efficacious for obesity management remains a top priority for the entire medical system.…”
mentioning
confidence: 99%